Chilean Complementary Feeding Program Reduces Anemia and Improves Iron Status in Children Aged 11 to 18 Months. Issue 4 (December 2013) - Brito, Alex; Olivares, Manuel; Pizarro, Tito; Rodríguez, Lorena; Hertrampf, Eva
Background: Iron deficiency is the most prevalent nutritional deficiency in the world, primarily affecting infants, young children, and women of childbearing age. Objective: To evaluate the impact of the National Complementary Feeding Program (NCFP) on anemia and iron status in Chilean children aged 11 to 18 months. Methods: Two studies were performed. The first study was performed at one public outpatient health center in Santiago, using data collected in 1999 ( n = 128) and 2000 ( n = 125), before and after the national introduction of iron-fortified milk. Subsequently, a study of a representative sample ( n = 320) from the two most populated areas of the country was performed in 2009. Results: One year after fortification, the prevalence of anemia was 9%; significantly lower ( p < .001) than the 27% prevalence observed 1 year before. Ten years after fortification, 14% of children were anemic and 77% of children with anemia (12% of all children) suffered from iron-deficiency anemia. In 2009, 11% of children consuming iron-fortified milk delivered by the NCFP (73%) were anemic, significantly lower ( p = .028) than the 21% prevalence of anemia observed in children without consumption. Consumption of iron-fortified milk was positively associated with hemoglobin concentration ( r = 0.28, p = .022) and was associated with a lower prevalence of anemia after adjusting for confounding factors (odds ratio, 0.50; 95% CI, 0.26 to 0.96). Conclusions: In Chile, the NCFP has had an impact on the reduction of anemia and improved the iron status of children aged 11 to 18 months. Increasing the consumption of this iron-fortified milk could enhance the impact of the NCFP.